Working with robots: trends and future directions - Wang, Siqi; Lim, Weng Marc; Cheah, Jun Hwa; Lim, Xin Jean (Elsevier, 2025)
Robots are taking on a prominent role in driving organizational evolution toward industrial revolutions. While research on the role of robots in human resource management (robot-HRM) is proliferating, the literature falls short in providing a state-of-the-art overview of the progress and ways forward for the field. Hence, this study aims to review and consolidate the extant literature on robot-HRM into a unified framework and provide pragmatic ways forward. To do so, this study conducts a framework-based systematic literature review by adopting the SPAR-4-SLR protocol to guide its assembling, arranging, and assessing of theories, contexts, characteristics, and methods (TCCM) of robot-HRM studies identified and retrieved from Scopus and Web of Science. In doing so, this study contributes a seminal overview of the research trends and ways forward for robot-HRM, as well as the implications for professionals to manage the embedding of robots and the interaction with employees in the workplace.